Environmental awareness and green carnival / E. Tavasuria Ekangovan - Ekangovan, E. Tavasuria (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2018)
Tapah, May 4, 2018, 10 students won the 'Anugerah Inovasi Pelajar' during the Environmental Awareness and Green Carnival programme which was organized by the Faculty of Applied Sciences, UiTM Perak Branch, Tapah Campus which involved 51 final year Biology stu-dents. The objectives of the programme were to meet the UiTM Vice-Chancellor's mandate for 2018: "Innova-tion and Sustainability Drive Global Excellence" and the National Transformation (TN50) that emphasise on inno-vation and environmental aspects. Besides that, the aim of the programme was to apply the knowledge of science and technology in inventing products that can reduce pollution, to use biodegradable and non-biode-gradable materials to reduce environmental pollution.